(untitled) (Bangladesh Journal of Medical Science, 2017)
Majority of acute viral hepatitis cases resolve spontaneously in due course of time. Few cases that develop acute liver failure are prone to develop various complications, including acute pancreatitis. However, development of acute pancreatitis in patients with uncomplicated acute viral hepatitis is very rare and extremely rare in case of Acute Hepatitis B. In this case, a young boy with acute non-fulminant hepatitis B developed acute moderately severe pancreatitis, diagnosed by clinical, enzymatic and radiological features. He was managed conservatively and improved. Acute pancreatitis must be considered in patients with acute viral hepatitis who develop abdominal pain. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.455-457